Random Practice Enhances Retention and Spatial Transfer in Force Field Adaptation - Herzog, Michael; Focke, Anne; Maurus, Philipp; Thürer, Benjamin; Stein, Thorsten (Frontiers in Human Neuroscience, 2022)
The contextual-interference effect is a frequently examined phenomenon in motor skill learning, but has not been extensively investigated in motor adaptation. Here, we first tested experimentally if the contextual-interference effect is detectable in force field adaptation regarding retention and spatial transfer, and then fitted state-space models to the data to relate the findings to the “forgetting-and-reconstruction hypothesis”. Thirty-two participants were divided into two groups with either a random or a blocked practice schedule. They practiced reaching to four targets and were tested 10 min and 24 h afterwards for motor retention and spatial transfer on an interpolation and an extrapolation target, and on targets which were shifted 10 cm away. The adaptation progress was participant-specifically fitted with 4-slow-1-fast state-space models accounting for generalization and set breaks. The blocked group adapted faster (p=0.007), but did not reach a better adaptation at practice end (p=0.927). We found better retention (10 min), interpolation transfer (10 min), and transfer to shifted targets (10 min & 24 h) for the random group (each p<0.05). However, no differences were found for retention or for the interpolation target after 24 h (p=0.275, p=0.237). Neither group showed transfer to the extrapolation target. The extended state-space model could replicate the behavioral results with some exceptions. The study shows that the contextual-interference effect is partially detectable in practice, short-term retention, and spatial transfer in force field adaptation; and that state-space models provide explanatory descriptions for the contextual-interference effect in force field adaptation.